A Novel Algorithm for the Evaluation of Corneal Nerve Beadings by in vivo Confocal Microscopy in Patients With Type 1 Diabetes Mellitus - Abicca, Irene; Giannini, Daniela; Gilardi, Marta; Roszkowska, Anna Maria; Parravano, Mariacristina; Picconi, Fabiana; Frontoni, Simona; Schiano-Lomoriello, Domenico (Frontiers in Medicine, 2022)
Purpose: Diabetes mellitus (DM) could be complicated by peripheral neuropathy. In vivo confocal microscopy (IVCM) is an ocular examination for the diagnosis of small fiber neuropathies and for the detection of earliest corneal sub basal nerve plexus (SBP) alterations. Corneal SBP characteristics include focal enlargement along the nerve fiber, called corneal beadings. These dilatations represent a mitochondrial accumulation induced by the reactive oxygen stress, as a consequence of hyperglycemia. For this reason, corneal beadings are considered indicative of metabolic activity. The aim of this study is to describe corneal characteristics of a population of type 1 diabetes mellitus (T1DM) well metabolically controlled, using a new algorithm for the analysis of corneal beading size (BS). Methods: Patients aged ≥18 years affected by T1DM, comparing them to healthy subjects underwent IVCM (Confoscan 4; Nidek Technologies Padova, Italy). Starting from the coordinates of the beadings, detected by the IVCM, we implemented a new algorithm for automatically measuring BS in corneal SBP images. Results: We compared 20 eyes of T1DM patients with 26 healthy controls. The corneal nerves fiber length (p=0.008), corneal nerves fiber length density (p=0.008) and the number of fibers (p=0.017) were significantly lower in the diabetic group respect controls. There was no difference between diabetic and healthy eyes in mean number of corneal beadings both in the frame of analysis (p= 0.606) and for 0.1 mm of SBP nerve (p=0.145). Regarding the BS, T1DM patients had corneal beadings larger than the controls (p=0.036). Conclusions: We found that the corneal beadings parameters are similar in healthy and T1DM. Nevertheless, measuring the BS with our algorithm, we showed that corneal beadings are enlarged in patients affected by T1DM when compared with healthy controls. Identifying beading expansion in corneal nerve fiber using IVCM should become a useful tool to predict peripheral neuropathy at early stage.